Endogenous histones function as alarmins in sterile inflammatory liver injury through Toll‐like receptor 9 in mice - Huang, Hai; Evankovich, John; Yan, Wei; Nace, Gary; Zhang, Lemeng; Ross, Mark; Liao, Xinghua; Billiar, Timothy; Xu, Jun; Esmon, Charles T.; Tsung, Allan (Hepatology (Baltimore, Md.), 2011)
Sterile inflammatory insults are known to activate innate immunity and propagate organ damage through the recognition of extracellular damage‐associated molecular pattern (DAMP) molecules. Although DAMPs such as endogenous DNA and nuclear high‐mobility group box 1 have been shown to be critical in sterile inflammation, the role of nuclear histone proteins has not yet been investigated. We report that endogenous histones function as DAMPs after ischemic injury through the pattern recognition receptor Toll‐like receptor (TLR) 9 to initiate inflammation. Using an in vivo model of hepatic ischemia/reperfusion (I/R) injury, we show that levels of circulating histones are significantly higher after I/R, and that histone neutralization significantly protects against injury. Injection of exogenous histones exacerbates I/R injury through cytotoxic effects mediated by TLR9 and MyD88. In addition, histone administration increases TLR9 activation, whereas neither TLR9 nor MyD88 mutant mice respond to exogenous histones. Furthermore, we demonstrate in vitro that extracellular histones enhance DNA‐mediated TLR9 activation in immune cells through a direct interaction. Conclusion: These novel findings reveal that histones represent a new class of DAMP molecules and serve as a crucial link between initial damage and activation of innate immunity during sterile inflammation. (HEPATOLOGY 2011; 54:999–1008)